ICT access during the COVID-19 pandemic in Paraguay: Educational actors’ perspectives - Canese, Valentina; Mereles, Juan Ignacio; Amarilla, Jessica (REVISTA PARAGUAYA DE EDUCACIÓN A DISTANCIA (REPED), 2021)
This article presents the main issues related to ICT access for educational actors (students, teachers and parents) in relation to the measures adopted by the government to address the COVID-19 pandemic. The purpose of this study is to examine their access to ICT at the moment of starting the interruption of the usual school activities due to the COVID-19. The participants included 505 parents of school children and youth from the pre-school to secondary, 1030 teachers from all educational levels and 856 students from secondary school and higher education at public, private and subsidized institutions throughout the country. For data collection, online questionnaires with closed-ended and open-ended questions were used, administered through different digital channels at the beginning of the confinement. Results show that up to 5% of the participants do not have cell phones and up to 31% do not have access to a computer to carry out the educational process without interruptions. Access to the Internet is restricted outside of the capital and its metropolitan area since limited data packages are used, which in turn prevent, in many cases, the adequate development of academic activities (48% of students, 40% of teachers and 51% of parents have limited connection). The most widely used medium for this purpose is the WhatsApp messaging app, especially at the non-university educational levels. This study shows that there are still educational actors, most from the interior of the country, whose access to the technological resources needed to carry out educational tasks during the pandemic is very limited and their connectivity restricted. The results of this study call on educational authorities to consider these factors when making decisions regarding the implementation of educational policies that require access to technology.